2021
DOI: 10.31219/osf.io/d3h8e
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting effects of methylphenidate and sulpiride on brain and cognition: A pharmaco-fMRI, PET study. Design and descriptives.

Abstract: The large variation observed in the effects of dopaminergic drugs poses a major problem for neuropsychiatry, where therapeutic drugs may be ineffective or detrimental in a proportion of patients, but also for the healthy population. We have conducted a pharmaco-fMRI/PET study in 100 healthy participants to investigate the neural and neurochemical mechanisms of this variability. We studied the cognitive effects of methylphenidate (20mg) and sulpiride (400mg) across various cognitive domains, such as reward lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Data were collected as part of a large PET, pharmaco-fMRI study on the effects of methylphenidate and sulpiride on brain and cognition, employing a within-subject, placebo- controlled, double-blind cross-over design. For a detailed description of the testing sessions and tasks and measures collected, see Määttä et al (2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were collected as part of a large PET, pharmaco-fMRI study on the effects of methylphenidate and sulpiride on brain and cognition, employing a within-subject, placebo- controlled, double-blind cross-over design. For a detailed description of the testing sessions and tasks and measures collected, see Määttä et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a larger project (Määttä et al, 2021), for which 100 healthy volunteers were recruited, 50 women and 50 men (age at inclusion: ranged 18 to 43, mean (SD) = 23.0 (5.0) years). All participants provided written informed consent and were paid 309 euro on completion of the overarching study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2021 [67]. The study was approved by the regional research ethics committee (Commisssie Mensgebonden Onderzoek, region Arnhem-Nijmegen; 2016/2646; ABR: NL57538.091.16).…”
Section: Methodsmentioning
confidence: 99%
“…The data reported here were acquired in the context of a larger pharmacological PET/fMRI study, components of which have been and will be reported separately (Hofmans et al, 2020(Hofmans et al, , 2022Määttä et al, 2021;van den Bosch, Hezemans, et al, 2022;van den Bosch, Lambregts, et al, 2022;Westbrook et al, 2020; an overview of the complete study at https://osf.io/d3h8e). For this study, participants paid five visits.…”
Section: General Proceduresmentioning
confidence: 99%